Proceedings of the Thirteenth Conference on Applied Linguistics (CONAPLIN 2020) 2021
DOI: 10.2991/assehr.k.210427.081
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Practice on Online Formative Assessment

Abstract: This paper aims to investigate (1) the struggles teacher encounters in his/her school's online formative assessments, and(2) the strategies teacher employs to deal with struggles in his/her school's online formative assessments. This research applied a qualitative study approach. A three year-experienced teacher who teaches 210 students in online teaching and learning has involved as the participant in this study. The data were gained from the interview to an EFL teacher of a school in Bandung. Result showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…All teachers agree that virtual learning environments have positive effects on education, but some challenges, too. In this point, similar results were identified by Nurfiqah et al (2021) wherein this virtual scenario, not all students are receiving appropriate feedback and applying the adequate corrections, besides learners feels in need of "Giving more time for speaking activities and feedback on these types of activities" (student 23).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…All teachers agree that virtual learning environments have positive effects on education, but some challenges, too. In this point, similar results were identified by Nurfiqah et al (2021) wherein this virtual scenario, not all students are receiving appropriate feedback and applying the adequate corrections, besides learners feels in need of "Giving more time for speaking activities and feedback on these types of activities" (student 23).…”
supporting
confidence: 68%
“…The ladder refers to new opportunities viewed as strategies, resources, and tools to assess students. Other studies conducted by Nurfiqah and Yusuf (2021) demonstrated that even when teachers agree on the importance of formative assessment, virtual classes impose enormous challenges for teachers when providing effective feedback. Also, they demonstrated that there is a disconnection between specific strategies and the learning results.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies of online formative assessment have been contextualized to concerns about the effectiveness and quality of online courses. For example, a work conducted by Bahati et al (2019) and Nurfiqah and Yusuf (2021) showed that technology was used to allow and promote creative formative assessment practice in real classroom settings. Hettiarachchi et al (2015) explained that online formative assessment is carried-out during learning, which provides practice for students on their learning in a course and possible development activities they could undertake to improve their level of understanding.…”
Section: Discussionmentioning
confidence: 99%